Hierarchical Authority of Indonesia’s Professional Disciplinary Board in Medical Malpractice: Ambiguity, Evidence, and Constitutional Legitimacy - Heru Cahjono; Prija Djatmika; Setiawan Noerdajasakti (UNISSULA, 2025)
Medical malpractice lies at the intersection of healthcare and criminal law. In Indonesia, Law Number 17 of 2023 on Health introduced the Professional Disciplinary Board (Majelis Disiplin Profesi/MDP), replacing the MKDKI and granting it expanded authority, including recommending criminal investigations. Article 308(1) requires a prior MDP recommendation before prosecution, positioning the MDP as a procedural gatekeeper while creating ambiguity over whether its examination is mandatory or discretionary.This study analyzes the hierarchical authority of the MDP in managing medical malpractice cases, focusing on the evidentiary challenges in proving criminal elements and their implications for criminal law reform. Using a normative juridical approach combining statutory, conceptual, and case analyses, the study finds that Article 308(1) creates a de jure mandatory MDP review requirement that operates as de facto discretionary, producing fundamental legal uncertainty, cases bypassing the MDP suffer from procedural invalidity concerns, evidentiary quality deficiencies due to loss of specialized technical review, and inconsistent judicial outcomes across different court levels, and the MDP's constitutional legitimacy as a pre-judicial gatekeeper is questionable due to insufficient procedural safeguards (14-working-day timeframe), unclear separation of powers between administrative and judicial functions, and violation of the lex certa (legal certainty) principle essential to criminal law